COVID-19 Prevention in People Living with HIV/AIDS: Entering the Endemic Phase - Manurung, Imelda F E; Takaeb, Afrona E L; da Cruz, Jermias (Kesmas, 2023)
The mortality and severity risks due to COVID-19 infection are higher in people living with HIV/AIDS (PLWHA) than those with no such condition. This study aimed to analyze the relationship between health literacy, social support, and the health belief model in PLWHA in preventing COVID-19 from entering the endemic phase. An analytic observational study with a cross-sectional design was conducted in October 2021 among 94 PLWHA selected by purposive sampling in Kupang City, Indonesia. The bivariate data analysis used the Chi-square, and the multivariate data analysis used the binomial logistic regression test. The results showed that 88.3% of the participants had poor COVID-19 literacy, 67% had low emotional support, and 71.3% had poor COVID-19 prevention behavior. The results of the multivariate analysis showed that the factors with the strongest association, COVID-19 literacy (95% CI = 1.71–108.55; PR = 4.15)and emotional support (95% CI= 1.01–53.81; PR = 2.35), improve COVID-19 prevention behavior. Implementing communication, information, education, and policy strategies is important to improve literacy and emotional support to prevent COVID-19 from entering the endemic phase among PLWHA.